Genome-wide, chromosome-naïve compartmentalization of major developmental networks tailored by modular placement of human embryo-regulatory Long Terminal Repeats - Gennadi V. Glinsky (Academia Molecular Biology and Genomics)
At inception, eukaryotes solved the conflict of the physical dimensions of meter-sized linear chromatin fibers placed into micron-sized nuclei by employing two mechanisms: (i) fragmenting genomic DNA into sets of shorter segments, called chromosomes; (ii) compacting each chromosome by folding it into 3D chromatin arrays. Despite this physical segregation, eukaryotic genomes possess an intrinsic regulatory connectivity that facilitates remarkable chromosome-naive function-aligned integration and striking developmental precision in conveying genetic information from conception and embryogenesis to adulthood. In this contribution, gene ontology-guided proximity placement analyses of 8839 highly conserved retroviral Long Terminal Repeat (LTR) elements fixed in human genomes and linked to 5444 down-stream target genes revealed chromosome-naive compartmentalization and function-aligned integration along major developmental networks of the global genomic regulatory dominion (GRD), components of which operate during human embryogenesis, development, and adulthood. Evolution forged the GRD into a functionally consonant constellation of 26 genome-wide multimodular genomic regulatory networks (GRNs), each of which is defined by significant enrichment of numerous single gene ontology (GO)-specific traits. GRN coordinates appear scattered across chromosomes, occupying 5.5–15.09% of the human genome. Each GRN harbors 529–1486 regulatory LTRs derived from LTR7, MLT2A1, and MLT2A2 sequences, which appear quantitatively balanced according to their genome-wide abundance. GRNs govern the activities of between 199 and 805 down-stream target genes, including transcription factors, chromatin-state remodelers, signal-sensing and signal transduction mediators, enzymatic and receptor-binding effectors, intracellular complexes and extracellular matrix elements, and cell–cell adhesion molecules. GRNs consist of several hundred to thousands of smaller, GO enrichment-defined genomic regulatory modules (GRMs), which include from a dozen to hundreds of LTRs and down-stream target genes. GRMs appear to operate along specific phenotypic avenues on the timescale of an individual’s life-span, exerting profound effects on patterns of transcription, protein–protein interaction, developmental phenotypes, physiological traits, and pathological conditions in Modern Humans. Overall, this study identifies 69,573 statistically significant regulatory LTR-linked GRMs (binominal FDR q-value threshold of 0.001), including 27,601 GRMs validated by single GO-specific directed acyclic graph (DAG) analyses across six GO annotations. Collectively, the reported observations support the hypothesis that pan-primate endogenous retroviruses have made significant impacts on the evolution of the global regulatory connectivity of GRNs affecting the physiological traits and pathological conditions of Modern Humans, including phenotypes whose manifestations are considered human-specific.